Life and Writings of Br. M. Rafael Barón (VI) - Arnáiz Barón, Rafael, Heiliger (Cistercian studies quarterly, 2002)
Presents the biography of priest Maria Rafael Barón. Spiritual life of Barón; Sufferings due to sickness; Power of prayer.